How should we measure addiction recovery? Analysis of service provider perspectives using online Delphi groups. (August 2014) - Neale, Joanne; Finch, Emily; Marsden, John; Mitcheson, Luke; Rose, Diana; Strang, John; Tompkins, Charlotte; Wheeler, Carly; Wykes, Til
<x xml:space="preserve">Abstract</x> Aims: To explore ways of measuring addiction recovery and the extent of agreement/disagreement between diverse service providers on potential recovery indicators. Methods: Separate online Delphi groups with (i) addiction psychiatrists (n = 10); (ii) senior residential rehabilitation staff (n = 9); and (iii) senior inpatient detoxification unit staff (n = 6). Each group was conducted by email and followed the same structured format involving three iterative rounds of data collection. Content analyses were undertaken and the results from each group were compared and contrasted. Findings: Indicators of recovery spanned 15 broad domains: substance use, treatment/support, psychological health, physical health, use of time, education/training/employment, income, housing, relationships, social functioning, offending/anti-social behaviour, well-being, identity/self-awareness, goals/aspirations, and spirituality. Identification of domains was very consistent across the three groups, but there was some disparity between, and considerable disparity within, groups on the relative importance of specific indicators. Conclusions: Whilst there is general consensus that recovery involves making changes in a number of broad life areas and not just substance use, there is substantial disagreement on particular measures of progress. Further studies involving other stakeholder groups, particularly people who have personally experienced drug or alcohol dependence, are needed to assess how transferable the 15 identified domains of recovery are.